Changes in brain network dynamics during functional/dissociative seizures: An exploratory pilot study on EEG microstates - Domantė Kučikienė; Johannes Jungilligens; Stefan Wolking; Yvonne Weber; Jörg Wellmer; Stoyan Popkirov (Epilepsy & Behavior Reports, 2025)
The pathophysiology of functional/dissociative seizures (FDS), also known as psychogenic nonepileptic seizures, remains incompletely understood. Current theories suggest that ictal changes in self-awareness and behavioural control are likely related to arousal-mediated disruptions of brain network dynamics, but direct electrophysiological evidence is scarce. In a proof-of-concept, the second of its kind pilot study, we explored ictal changes in EEG microstates – quasi-stable patterns of electrical activity of 50–70 ms duration that represent fundamental building blocks of large-scale brain network dynamics. Across a sample of 13 FDS patients, four microstates yielded a high mean global explained variance of 76.2 % and qualitatively resembled the well-established “canonical” microstate map topographies A-D. Repeated measure analysis of variance did not reveal any significant differences in contribution, occurrence or global field power of microstates between baseline and ictal recordings. Microstate duration, however, was significantly different between baseline and seizure recordings with shorter durations of microstates in FDS (p = 0.007). This was most pronounced for microstate D (Cohen’s d = 0.75) with the change being significant in an exploratory post hoc paired t-test (p = 0.044). Since microstate D is thought to reflect frontoparietal network activity, the findings of this pilot study can be interpreted as supportive of current theories of arousal-mediated disruptions of network activity that reduce cognitive and behavioural control during FDS.